Communication about HIV and death: Maternal reports of primary school-aged children's questions after maternal HIV disclosure in rural South Africa - Rochat, T; Mitchell, J; Lubbe, A; Stein, A; Tomlinson, M; Bland, R (Elsevier, 2016)
Introduction Children's understanding of HIV and death in epidemic regions is under-researched. We investigated children's death-related questions post maternal HIV-disclosure. Secondary aims examined characteristics associated with death-related questions and consequences for children's mental health. Methods HIV-infected mothers (N = 281) were supported to disclose their HIV status to their children (6–10 years) in an uncontrolled pre-post intervention evaluation. Children's questions post-disclosure were collected by maternal report, 1–2 weeks post-disclosure. 61/281 children asked 88 death-related questions, which were analysed qualitatively. Logistic regression analyses examined characteristics associated with death-related questions. Using the parent-report Child Behaviour Checklist (CBCL), linear regression analysis examined differences in total CBCL problems by group, controlling for baseline. Results Children's questions were grouped into three themes: ‘threats’; ‘implications’ and ‘clarifications’. Children were most concerned about the threat of death, mother's survival, and prior family deaths. In multivariate analysis variables significantly associated with asking death-related questions included an absence of regular remittance to the mother (AOR 0.25 [CI 0.10, 0.59] p = 0.002), mother reporting the child's initial reaction to disclosure being “frightened” (AOR 6.57 [CI 2.75, 15.70] p=<0.001) and level of disclosure (full/partial) to the child (AOR 2.55 [CI 1.28, 5.06] p = 0.008). Controlling for significant variables and baseline, all children showed improvements on the CBCL post-intervention; with no significant differences on total problems scores post-intervention (β -0.096 SE1.366 t = -0.07 p = 0.944). Discussion The content of questions children asked following disclosure indicate some understanding of HIV and, for almost a third of children, its potential consequence for parental death. Level of maternal disclosure and stability of financial support to the family may facilitate or inhibit discussions about death post-disclosure. Communication about death did not have immediate negative consequences on child behaviour according to maternal report. Conclusion In sub-Saharan Africa, given exposure to death at young ages, meeting children's informational needs could increase their resilience.